DOMESTIKASI IKAN KAPAR (Belontia hasselti) YANG TERTANGKAP DI SUNGAI SEBANGAU - Frid Agustinus; Infa Minggawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
The Kapar fish (Belontia hasselti) is the consumption fish that is obtained only on wild caught. Not yet succeeded in culture this fish, so domestication is needed as an early stage of the aquaculture. The purpose of this research was to knowning the stages of domestication of Kapar fish caught from the Sebangau river in the process of adaptation to new habitats in semi-permanent ponds which is seen from the observation of water quality as well as the growth and survival rate of the Kapar fish. Environmental adaptation for culture fish is the key to successful domestication. Observations of water quality in the fish's wild habitat with the quality of the water where the fish adapt in the pond are slightly different, especially the DO and pH values, but the water quality is still within the tolerance of the Kapar fish to live. The water quality parameters show the temperature in the range 27-29 °C, DO in the range 3-4.2 mg.L-1, and pH in the range 7-7.4. The growth in length and weight during the research showed that the fish were able to adapt feeding. The length and an average weight of Kapar fish until the research were 12.1 cm in length and 31.4 g of weight and it was known that during the research period the absolute length growth of Kapar fish was 1 cm and the absolute weight growth was 8 g . Results of data analysis carried out during the research that the survival rate of Kapar fish is 83 %.